Od Boga El do kultu jedynego Jahwe - Lemański, Janusz (Verbum Vitae, 2003)
Recenzja: M.S. Smith, The Origin of Biblical Monotheism. Israel's Polytheistic Background and the Ugaritic Texts, Oxford University Press; Oxford 2001.